Evaluation of a poly-herbal preparation for the treatment of peptic ulcer - Hayat, Zaman; Chaudhry, Mueen Ahmad; Alamgeer, . (Bangladesh Journal of Pharmacology, 2017)
The aim of this study was to validate the traditional uses of ulcerene, a poly-herbal formulation in ethanol, aspirin and stress-induced gastric ulcer model of rat. The extent of gastric ulcer formation was studied, using ulcer score, ulcer index, percentage cure through gross examination and histopathological evaluation. A significant (p<0.001) dose-dependent anti-ulcerant effect was observed in ulcerene (50 and 100 mg/kg)-treated group with highest effectiveness against ethanol-induced ulcer. The concentration-dependent spasmolytic effect was seen in spontaneously contracting, high K+ (80 mM) and carbachol (1 µM)-induced jejunum contractions (10, 0.3 and 1 mg/mL), similar to dicyclomine (10, 1 and 3 µM), indicated non-specific spasmolytic mechanism behind the effect. By considering these results, ulcerene can be suggested for the treatment of peptic ulcer.